How to win the Olympic Games: the empirics of key success factors of Olympic bids - Arne Feddersen; Wolfgang Maennig; Philipp Zimmermann (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This paper examines the probability of the success of city bid campaigns on the basis of quantified determinants for a total of 48 bids for the Summer Olympic Games between 1992 and 2012. Using a model comprising the distance of sporting venues from the Olympic Village, local temperatures and unemployment rates, we can correctly predict the decision for 100% of failed bids and 50% of successful bids.
Keywords: L83; C25; 330; Olympic Games; Bidding process; Key success factors; Binary logistical regression